PENGARUH MOTIVASI TERHADAP PRESTASI SISWA DI MA MA’ARIF RANDUBLATUNG - Mohammad Imam Mudi Al Ghofiqi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
The objectives of this research are to 1) find out the profile of student’s learning motivation in Physics class and out class measured by aspects such as Attention, Relevation, Confidence, and Satisfaction; and 2) measure the percentage of each learning motivation aspect such as Attention, Relevation, Confidence, and Satisfaction contributed to students’ learning motivation in Physics class and out class.